Novel Symmetric and Asymmetric Multilevel Inverter Topology for Permanent Magnet Synchronous Motor - Aparna Prayag; Sanjay Bodkhe (Institute of Advanced Engineering and Science, 2017)
In this paper a new, simple multilevel inverter topology is proposed. Multilevel inverter uses several dc sources and power switches to synthesize desired output voltage waveform. The single phase structure of proposed topology in this paper consists of two dc sources and eight power switches. When the magnitudes of dc sources are equal it operates in symmetric mode, however in order to increase output voltage levels unequal magnitudes of dc sources are selected, then it operates in asymmetric mode. So far, multilevel inverter topologies have been used in motor drive industry to run induction motors. Recently permanent magnet synchronous motors (PMSM) are replacing induction motors. Multilevel inverter is an attracting choice for driving high performance PMSM. However very few studies discuss the performance of multilevel inverter fed PMSM. In this paper simulation of novel symmetric and asymmetric multilevel inverter is carried out to analyze performance of PMSM. The topology is investigated through computer simulation using MATLAB/Simulink.